Question 18

If$$\ a^{2}+b^{2}+c^{2}$$= 2(a-b-c)-3, then the value of 4a - 3b + 5c is


$$\ a^{2}+b^{2}+c^{2}$$= 2(a-b-c)-3
We can write the above equation as

$$ a^{2}-2a+1+b^{2}+2b+1+c^{2}+2c+1$$=0
$$\Rightarrow (a-1)^{2}+(b+1)^{2}+(c+1)^{2}$$=0

$$(b+1)^{2}$$=0$$\Rightarrow$$ b=-1
$$(c+1)^{2}$$=0$$\Rightarrow$$ c=-1

4a-3b+5c= 4(1)-3(-1)+5(-1)=4+3-5=2

Create a FREE account and get:

  • Free SSC Study Material - 18000 Questions
  • 230+ SSC previous papers with solutions PDF
  • 100+ SSC Online Tests for Free


Boost your Prep!

Download App